Sosialisasi Peran Guru dan Penanganan Dalam Mengatasi Kesulitan Pembelajar Jarak Jauh Bagi Siswa Berkebutuhan Khusus Era Pandemi Covid-19 Pada MTs Al Muhajirin - Andrie Kurniawan; Agustiena Merdekawati; Al Ghazali; Jasmine Celia Sahfitri (Jurnal Pengabdian Masyarakat Formosa, 2022)
Inclusion education is an alternative to students with special needs. The problems faced are: 1. Lack of supporting facilities. 2. Mastery of knowledge and skills that teachers lack. 3. The educational curriculum has not helped children who have the ability to have disabilities or special needs. This training focuses on this which is carried out by MT's Al Muhajirin Jl. Haur Jaya I No. 1 Rt. 01 Rw. 07 Kel. Kebon Pedes Kec. Tanah Sareal Bogor City, West Java Province. With this socialization, it is a beginning to find out the role of teachers in overcoming the difficulties of distance learning for those with special needs.